Entre a responsabilidade social empresarial (RSE) e o negócio social (NS): estudo de caso de uma Cooperativa em Açucena - MG - Batista, Jéssica da Cruz (2018)
This study seeks to understand how the Corporate Social Responsibility (CSR) actions of a pulp company can contribute to the emergence of social business (NS) in the form of a food production cooperative in the Municipality of Açucena - MG. For this resea